Wnt3a Enhances Mesenchymal Stem Cell Engraftment and Differentiation in a Chronic Obstructive Pulmonary Disease Rat Model - Wu H; Zhong Y; Li Y; Zhou X; Zhao T; Wan D; Zhu Y; Zhang Z; Li X; Gan X (International Journal of COPD)
Huala Wu,1,* Yulan Zhong,2,* Yangjingsi Li,3 Xiangxiang Zhou,2 Tiantian Zhao,1 Daomou Wan,1 Yuanzhe Zhu,1 Zhiyan Zhang,1 Xiaolei Li,1,4 Xin Gan1,4 1Department of Respiratory and Critical Care Medicine, Jiangxi Provincial Key Laboratory of Respiratory Diseases, Jiangxi Institute of Respiratory Diseases, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Chest Hospital of Jiangxi Province, Nanchang, Jiangxi, 330006, People’s Republic of China; 3Department of Respiratory and Critical Care Medicine, Jiangxi Provincial People’s Hospital, Nanchang, Jiangxi, 330006, People’s Republic of China; 4China-Japan Friendship Jiangxi Hospital, National Regional Center for Respiratory Medicine, Nanchang, Jiangxi, 330200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Gan; Xiaolei Li, Email ganxin1207@126.com; xiaoleili1225@163.comBackground: Bone marrow mesenchymal stem cell (BMSC) therapy is a novel approach for treating COPD. However, the difficulty in engraftment and easy clearance of BMSCs in vivo has hindered their clinical application. Hence, exploring effective methods to improve the engraftment and differentiation rates of BMSCs in vivo is urgent.Methods: We constructed BMSCs overexpressing Wnt3a by lentivirus infection and transplanted them into a COPD rat model. The damage level of COPD rat lung tissue was assessed by pathology analysis and inflammatory cytokines analysis. The engraftment of BMSC was detected by immunofluorescence staining. Statistical analysis was performed using GraphPad Prism 7.Results: We found that Wnt3a significantly enhanced the engraftment rate of BMSCs in the lungs of rats and further increased their differentiation rate into type II alveolar epithelial cells. We also assessed the expression of inflammatory factors in the lung tissues of COPD rats and discovered that Wnt3a reduced the levels of the inflammatory factors IL-6 and IL-1β while increasing the level of the anti-inflammatory factor IL-10. Our study demonstrates that Wnt3a can improve the engraftment and differentiation rates of BMSCs in the host and further alleviate COPD symptoms by regulating the secretion of inflammatory factors.Conclusion: Constructing BMSCs overexpressing Wnt3a could serve as a new strategy for stem cell therapy in COPD.Keywords: Wnt3a, BMSCs, COPD, inflammatory cytokines